2017
DOI: 10.31234/osf.io/8df2m
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Injury talk: spontaneous parent-child conversations in the aftermath of a potentially traumatic event

Abstract: Background While talking about traumatic experiences is considered central to psychological recovery, little is known about how these conversations occur in daily life. Objective We investigated spontaneous injury talk among parents and children in the aftermath of a child's hospitalisation due to physical trauma, and its relationship with children's socioemotional functioning. Methods In a prospective naturalistic observation study, we audio-sampled the daily life of 71 families with the Electronically Activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…The majority of parents in our study described spontaneously engaging in trauma-focused conversations with their children as a positive way to facilitate child coping, consistent with previous evidence suggesting that in the aftermath of an acute event, trauma talk is common for many families (Alisic et al, 2017;Williamson et al, 2016). This largely positive view of trauma conversations also extended to the structured narrative task, which was perceived as creating an opportunity for the child to engage in a conversation about their trauma if they had not already, or to talk more deeply about their emotions, helping to process their reactions.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The majority of parents in our study described spontaneously engaging in trauma-focused conversations with their children as a positive way to facilitate child coping, consistent with previous evidence suggesting that in the aftermath of an acute event, trauma talk is common for many families (Alisic et al, 2017;Williamson et al, 2016). This largely positive view of trauma conversations also extended to the structured narrative task, which was perceived as creating an opportunity for the child to engage in a conversation about their trauma if they had not already, or to talk more deeply about their emotions, helping to process their reactions.…”
Section: Discussionsupporting
confidence: 89%
“…For children, parents are a key source of informal support following trauma exposure (Williamson, Creswell, Butler, Christie, & Halligan, 2017). Recent work that recorded daily conversations of children exposed to acute trauma found that families initially spent an average of 46 minutes per day discussing the child's injury and the emotions associated with it (Alisic et al, 2017). Other evidence indicates that too much or too little trauma talk can potentially lead to higher levels of child distress posttrauma (Stein et al, 2004;Wilson, Lengua, Meltzoff, & Smith, 2010).…”
Section: 伤叙述任务描述为一个可以与孩子开始对话,了解孩子的感受以及让孩子处理创伤的机 会。然而,对于一些父母或孩子来说,这项任务mentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, the authors explained that they increased the number of coders to six per participant after low initial inter-coder reliability with three coders per participant, and commented that some of the dimensions (e.g., neuroticism) were difficult to detect acoustically. Other investigators have rated the degree of specific emotions expressed (e.g., upset or happy; 5-point scale), maternal responsiveness (a composite comprised of expressed warmth, emotional support, and pride; 5-point scale), and the overall emotional tone of an interaction (ranging from negative to positive; 7-point scale) in each sound file with acceptable to excellent inter-coder agreement (Alisic et al, 2015(Alisic et al, , 2017Farrell et al, 2019;Mangelsdorf, Mehl, Qiu, & Alisic, 2019;Tobin et al, 2015a;Tobin et al, 2015b).…”
Section: Figure 1 Steps To Coding and Processing Ear Data Ear Codingmentioning
confidence: 99%